Modelling the Dynamics of Exchange Rates and GDP in Nigeria: A Single Equation Error Correction Model (ECM) Analysis - Stephem, Mathew; Idi, Danjuma (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
This study eval_uates the effect of exchange rates on Nigeria's economic growth between 1990 and 2020 was examined. The exchange rate was limited to the nominal exchange rate, and real gross domestic product was used as a proxy for the growth of the economy. Secondary data were collected from the Central Bank of Nigeria statistical bulletin for the period of the study. The OLS regression and Granger Causality test were used for analysis in the study. The findings demonstrated that one of the two explanatory variables, exchange rate, has a substantial significant effect on economic growth. The causality test also showed that there is two-way causality between exchange rate and the economic growth. The study concludes that increase when there is increase in exchange rate, the economic growth (GDP) will increase in Nigeria since exchange rate is and essential and significant predictor of economic growth.